Phytochemical prospecting, modulator and antibacterial activity of aminoglycosides of the extract and fractions of the Annona squamosa - souza, Heloisa; Fernandes, Cicera; Tintino, Saulo; Morais-Braga, Maria Flaviana; Araújo, Antonia; Coutinho, Henrique; Menezes, Irwin; Kerntopf, Marta (Ethnobiology and Conservation, 2013)
The medicinal plants and natural products are products with a great scientific interest due their possible use like phytodrugs. In this context, the phytochemical composition and the antibacterial and antibiotic modulatory activity of the extract and fractions of Annona squamosa against Staphylococus aureus and Escherichia coli were performed. All natural products have not showed clinically relevant antibacterial activity, with MIC ≥ 1024 mg/mL. However, the extract combined with some aminoglycoside showed a synergistic effect against multiresistant strains E. coli 27 and S. aureus 358. Due these results, A. squamosa (Annonaceae) must be more studied to be used as a source of natural products with adjuvant potential to enhance the antibiotic activity, combating by this way the microbial antibiotic resistance.